Mechanical sensing protein PIEZO1 regulates bone homeostasis via osteoblast-osteoclast crosstalk - Lijun Wang (Nature Portfolio, 2020)
Mechanical forces induce bone remodeling, but how bone cells sense mechanical signaling is unclear. Here, the authors show that loss of the mechanotransduction channel Piezo1 in osteoblastic cells impairs osteoclast activity via YAP signaling and collagen expression, leading to reduced bone mass and spontaneous fractures.